2018
DOI: 10.1177/0898010118793465
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness: Assessing the Feasibility of a Pilot Intervention to Reduce Stress and Burnout

Abstract: The improvement in scores for the MBI measures were a positive finding. The intervention was low cost, individualized, and accessible. The feasibility and perceptions of the intervention's effectiveness has positive implications for the well-being of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 36 publications
1
28
0
2
Order By: Relevance
“…Several authors observed medium–high initial levels of D, which after the intervention had decreased by 7–17.60% (Gauthier et al, ; Mealer et al, ; Norouzinia et al, ). However, other authors observed medium–low levels for this parameter, with no significant changes following the intervention (Cohen‐Katz et al, ; Mackenzie et al, ; Montanari et al, ; Poulin et al, ; Watanabe et al, ).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Several authors observed medium–high initial levels of D, which after the intervention had decreased by 7–17.60% (Gauthier et al, ; Mealer et al, ; Norouzinia et al, ). However, other authors observed medium–low levels for this parameter, with no significant changes following the intervention (Cohen‐Katz et al, ; Mackenzie et al, ; Montanari et al, ; Poulin et al, ; Watanabe et al, ).…”
Section: Resultsmentioning
confidence: 89%
“…In all cases, decreased levels of EE were reported following the mindfulness intervention. The sample populations initially presented medium–high levels of EE, ranging from 42–69% (Mealer et al, ; Montanari et al, ). Mackenzie et al () and Norouzinia, Ramezani, Khalili, Dehghani, and Sharifi () also observed medium–high levels of EE, with mean scores of 26.38 and 29.27 points, respectively, for this dimension of burnout.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations